A Reliable Transport Protocol with Prediction Mechanism for Urgent Information in Wireless Sensor Networks - Zhenchun Wei; Lin Feng; Jianghong Han; Xiangwei Xu; Hao Peng (International Journal of Distributed Sensor Networks)
A reliable transport protocol with prediction mechanism for urgent information (PMUI) in WSNs is proposed. With PMUI, which is based on RTP-UI, the congestion control mechanism is improved, and the priority control and prediction mechanisms are adopted by taking the current queue length with change rate and expected queue length with remaining length together into consideration. The congestion status of current queue is analyzed and the changing trend of the next cycle of the queue is predicted as well. In order to evaluate the degree of congestion, state machine is adopted. Working states of WSNs are classified into eight states in accordance with different degrees of congestion. According to the change rate of a queue and the expected change rate of a queue, different rate adjustment mechanisms and bandwidth allocation schemes based on different working states are developed. Simulation results show that PMUI is lower than RTP-UI in both packet loss rate and the average delay for reliable transmission of urgent information.